(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Recruitment and selection is a backbone of human resource management (HRM) practices and its incorporation to business is vital to organizational success. When people sense the difficulty in cracking the interview it is related to unfairness and unethical hiring during the selection process. This paper examines the difference between ethics, Morals and values which people boast about while making important business decisions like hiring. A decision of recruitment that is becoming the burden is exercising unethical hiring practices. Most unethical hiring practices occur when a company decides to hire an employee based on his or her race, color, religion, appearance sex or national origin. This paper examines the patterns which people adapt for hiring to face the challenge and beat the competition in the industry. A secondary research has been conducted with an objective to analyze why people engage in discriminatory acts while hiring. It has been found that employees sometimes feel pressure to sacrifice ethics in today’s competitive market place due to increased expectations and cutbacks. unethical hiring during the selection process. It has been Understanding the major causes of unethical practices in the workplace will help us become sensitive to signals of escalating pressure to compromise our values. These values change occasionally and are not lived by, for which the excuse is always financial but that is not the cause of adapting unethical behavior.